Tridimensional Leadership Maturity: Analyzing Spiritual, Emotional, And Moral Dimensions of Female Principals in Indonesia's Transform School Program - Kartiwi, Asti Putri; Banu, Shamsiah; Sary, Fetty Poerwita; Sutopo, Timbul Wahyu (International Journal of Educational Management and Innovation, 2025)
Background. Despite female teachers comprising the global teaching workforce majority, significant gender disparities persist in educational leadership positions, necessitating holistic approaches integrating spiritual, emotional, and moral intelligence for effective educational transformation. This study aims to analyze tridimensional spiritual leadership implementation by female principals at SDN 72 and SDN 76 Central Bengkulu District within Indonesia's "Sekolah Penggerak" (Transform School) Program, examining how spiritual, moral, and emotional intelligence dimensions integrate in educational leadership contexts. Methods. A descriptive quantitative approach employed saturation sampling of 26 teachers and educational staff, utilizing a 36-item structured questionnaire measuring spiritual, moral, and emotional maturity dimensions across both institutions. Results. Demonstrated a hierarchical leadership profile where moral maturity achieved "excellent" ratings (M = 3.23), spiritual maturity scored "good" (M = 3.19), while emotional maturity emerged as a priority development area requiring improvement (M = 2.73, SD = 0.89) with notable inter-institutional disparities between schools. Moral maturity functioned as a catalytic force strengthening other leadership dimensions, confirming ethical foundations' critical importance in comprehensive leadership excellence within educational transformation initiatives. The study Conclusion. that tridimensional spiritual leadership requires balanced development across all dimensions, with moral maturity serving as the foundational element that enables spiritual and emotional intelligence integration, providing empirical evidence for multidimensional leadership models in Indonesian educational reform contexts and informing leadership development strategies for female educational leaders.